2018
DOI: 10.1038/s41598-018-28030-8
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of visible-light polarization with dendritic cell-cluster metasurfaces

Abstract: Cross-polarization conversion plays an important role in visible light manipulation. Metasurface with asymmetric structure can be used to achieve polarization conversion of linearly polarized light. Based on this, we design a quasi-periodic dendritic metasurface model composed of asymmetric dendritic cells. The simulation indicates that the asymmetric dendritic structure can vertically rotate the polarization direction of the linear polarization wave in visible light. Silver dendritic cell-cluster metasurface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…where t xx and t xy represent transmission coefficients for X to X and X to Y polarization conversion as shown in Equations (4) and (5), respectively. ϕ xx and ϕ xy are phase angles corresponding to t xx and t xy , respectively.…”
Section: Principle Of Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…where t xx and t xy represent transmission coefficients for X to X and X to Y polarization conversion as shown in Equations (4) and (5), respectively. ϕ xx and ϕ xy are phase angles corresponding to t xx and t xy , respectively.…”
Section: Principle Of Operationmentioning
confidence: 99%
“…With the advancement in THz sources and detectors, these investigations have gained great interest from researchers. Polarization manipulators, in their applications to rotate or convert polarization states of electromagnetic waves, have been comprehensively explored for stealth, cloaking and in diode-like applications [5][6][7][8]. Circular polarization is a preferred choice for THz wireless communication due to its lower sensitivity towards multipath fading and polarization mismatch with receiver mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such applications are excellent lenses [7], an invisibility cloak [8], a superior absorber [9], and a PC [10]. So far, PCs relying on MS structures have been utilized in the microwave [10], infrared [11], and visible regimes [12], [13] due to their flexible and easy profile.…”
Section: Introductionmentioning
confidence: 99%
“…These steps are towards more complex quantum system to control scalable quantum technologies [14]. In recent research photonic structures, metasurfaces [15] and dendritic cell clusters [16] are found useful for manipulation, transmission, and absorption of light. These metasurfaces give additional degrees of freedom to the polarization of light [17].…”
Section: Introductionmentioning
confidence: 99%